Association between ADORA2A gene polymorphisms and schizophrenia in the North Chinese Han population - Miao, Junxiao (Neuropsychiatr Dis Treat, 2019)
BACKGROUND: A large number of studies have shown a close relationship between ADORA2A and the pathological mechanism of schizophrenia. However, to our knowledge, there has been no studies examining the association between the ADORA2A gene and schizophrenia in Chinese Han population. PURPOSE: The objective of this study was to examine the relationship between adenosine A2A receptor (ADORA2A) single nucleotide polymorphisms and schizophrenia in the North Chinese Han population. PATIENTS AND METHODS: We detected ADORA2A single nucleotide polymorphisms (SNPs) using polymerase chain reaction-restriction fragment length polymorphism analyses and summarized our results using SPSS statistical software and Haploview in schizophrenia case group (n=398) and healthy control group (n=535). RESULTS: The frequency of the CC homozygote genotype of SNP rs2298383T/C were significantly higher in the case than the control group (p=0.005, OR=1.712, 95% CI=1.172–2.502). After linkage disequilibrium analysis, SNPs rs5996696A/C and rs2298383T/C displayed strong linkage disequilibrium. We found that the frequencies of haplotypes TA (χ(2)=6.268, p=0.0123) and CA (χ(2)=7.012, p=0.0081) were significantly higher in the case group than in the control group. CONCLUSION: In conclusion, SNPs in the ADORA2A gene may be associated with schizophrenia in the northern Chinese Han population.